Changes in the prevalence of human papillomavirus following a national bivalent human papillomavirus vaccination programme in Scotland: a 7-year cross-sectional study. Issue 12 (December 2017) - Kavanagh, Kimberley; Pollock, Kevin G; Cuschieri, Kate; Palmer, Tim; Cameron, Ross L; Watt, Cameron; Bhatia, Ramya; Moore, Catherine; Cubie, Heather; Cruickshank, Margaret; Robertson, Chris
Summary: Background: On Sept 1, 2008, Scotland launched routine vaccination for human papillomavirus (HPV) types 16 and 18, targeted at 12–13-year-old girls, of whom 92·4% were fully vaccinated in 2008–09. In this study, we report on vaccine effectiveness of the bivalent vaccine in these vaccinated women who attended for routine cervical screening at age 20–21 years. Methods: In this 7-year cross-sectional study (covering birth cohorts 1988–1995), we sampled approximately 1000 samples per year from those attending cervical screening at age 20–21 years and tested each for HPV. By linkage to vaccination records we ascertained prevalence by birth cohort and vaccination status. Estimates of vaccine effectiveness for HPV types 16 and 18, HPV types 31, 33, and 45, other high-risk types, and any HPV were calculated using logistic regression. Findings: In total, 8584 samples were HPV genotyped. Prevalence of HPV types 16 and 18 reduced substantially from 30·0% (95% CI 26·9–33·1) in the 1988 cohort to 4·5% (3·5–5·7) in the 1995 cohort, giving a vaccine effectiveness of 89·1% (85·1–92·3) for those vaccinated at age 12–13 years. All cross-protective types showed significant vaccine effectiveness (HPV type 31, 93·8% [95% CI 83·8–98·5]; HPV type 33, 79·1% [64·2–89·0]; HPV type 45, 82·6% [61·5–93·9]). Unvaccinated individuals born in 1995 had a reduced odds of HPV types 16 and 18 infection compared with those born in 1988 (adjusted odds ratio 0·13 [95% CI 0·06–0·28]) and reduced odds of HPV types 31, 33, and 45 (odds ratio 0·45 [0·23–0·89]). Interpretation: Bivalent vaccination has led to a startling reduction in vaccine and cross-protective HPV types 7 years after vaccination. There is also evidence of herd protection against the vaccine-specific and cross-protective types in unvaccinated individuals born in 1995. These findings should be considered in cost-effectiveness models informing vaccine choice and models to shape the future of cervical screening programmes. Funding: Scottish Government and Chief Scientists Office.